Submandibular Approach for Tracheal Intubation in Oro-maxillofacial Surgery: An Initial Experience in a Dental College Hospital in Bangladesh - Hossain, Md Shahadat; Begum, Hasina; Haider, Ismat Ara; Sarker, Md. Selim (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Tracheal intubation in oro-maxillofacial surgery is an important issue during operation. Objective: The purpose of the present study was to demonstrate the feasibility and the reliability of submandibular tracheal intubation as an alternative method for airway management in oro-maxillofacial surgery. Methodology: This clinical trial was conducted in the Department of oromaxillofacial Surgery at Dhaka Dental College and Hospital, Dhaka from January 2010 to June 2011 for a period of one and half year. Patients suffering from painful fractures associated with displaced nasal fracture were selected as study population. Results: A total number of 9 patients were recruited for this study of which 1 was female and 8 were males and the age range was between 16 to 51 years. The technique was found easy and offers a secure airway to the anaesthetist, an optimal operating field and an opportunity to check the dental occlusion with limited morbidity for the patient. In all patients the submandibular tracheal tube was extubated after the operation without complications or difficulties. Accidental dislodgement of the tube to the right main bronchus occurred in one patient while carrying out the procedure. It was rapidly detected and corrected. No other complications were encountered. Conclusion: Submandibular tracheal intubation is a safe, simple and effective technique for upper airway management when both oral and nasal tracheal intubations are not convenient in some oromaxillofacial surgery. Journal of National Institute of Neurosciences Bangladesh, 2015;1(2): 41-46